Comparative study of telmisartan and amlodipine to assess the effect on blood pressure, lipid profile and blood glucose level in Indian hypertensive patients - Neeraj Tripathi; Sangita Bohara; R. R. Singh; Anoop Kumar; Pooja Dhoan; D. Uraiya (International Journal of Medical Research and Review, 2016)
Introduction: Hypertension is emerging as a major health problem and while treating a patient with hypertension it is not only necessary to control blood pressure but also treat the associated risk factors which lead to metabolic syndrome.Methods: A randomized comparative study was designed to evaluate the effect of telmisartan on blood pressure (BP), lipid profile and blood glucose levels in hypertensive patients. This was compared with amlodipine with 1:1 randomisation. BP>140mm Hg (systolic) and >90mm Hg (diastolic) as well as body mass index (BMI) was taken in consideration. Blood sugar levels, lipid profile and urine samples were collected for protein and sugar. These samples were collected at baseline (first visit) and after 6 months.Results: The mean value of systolic BP in telmisartan group decreased from baseline by 17.43% (p<0.001) and 13.79% in diastolic BP (p<0.001). On comparing with amlodipine, telmisartan reduced mean systolic BP significantly more by 8.42% (p<0.001) and 5.59% (p<0.001) in diastolic BP. The mean fasting sugar level in patients with telmisartan group after 6 months was 100.70mg% which decreased by 10.27% (p<0.01) from baseline The effect of post prandial sugar level in telmisartan group was a reduction of 5.57mg% from baseline (p<0.001). There was significant reduction in mean value of urinary protein from 160.22mg% to 92.22 mg% (p<0.001).Conclusion: Besides significant reduction in BP, telmisartan also had beneficial effects on various metabolic parameters, where amlodipine was not effective. The salutary effects of telmisartan on the metabolic profile may be additional attribute beyond its established antihypertensive effect.